BELAJAR BAHASA KEDUA ATAU BAHASA ASING DENGAN MIND MAP YANG KREATIF DAN IMAJINATIF - Husniah Ramadhani Pulungan (IAIN Padangsidimpuan, 2014)
his research explained about how is to learn second language or another language with using Mind Map that creative and imaginative. Mind Map that will be analyzed in this research is one of the some alternative methods in studying new language. With Mind Map, someone can make his/her comprehending is simpler in studying one material with relax feeling, comfortable, and enjoyable. Mind Map can also drill positive attitude of people, like classify, remember, take a note, comprehend, imagine, interest, manage, and creative that useful in life.